State budget expenditures under martial law: Case of Ukraine - Igor Chugunov; Iryna Liubchak; Andriy Vatulov; Mykhailo Titarchuk; Valeriy Chugunov; Svitlana Zaychuk (Public and Municipal Finance, 2025)
The direction of the state budget to defense and the military-industrial complex under martial law imposes more stringent requirements on the system of formation and execution of state budget expenditures. The study aims to determine the efficiency of the distribution of state budget expenditures and their impact on the country’s macroeconomic stability under martial law. To evaluate the implications of martial law on the expenditure component of Ukraine’s state budget, a correlation regression analysis was employed to investigate the relationship between the budget deficit and the levels of total state budget expenditures and defense spending. The empirical findings indicate that fluctuations in state budget expenditures are a significant determinant of the budget deficit. In particular, a 1 billion UAH increase in total expenditures is associated with an average rise in the budget deficit of 1.19%. This result underscores the importance of a sound fiscal policy that ensures the efficient and rational allocation of budgetary resources, particularly under conditions of heightened military and security needs. Based on analytical results, medium-term budgetary projections for the period of 2025–2027 were developed. The forecast estimates that state budget expenditures will constitute approximately 45.74% of GDP, while the budget deficit is projected to reach 18.84% of GDP. The findings emphasize the need for effective expenditure management and strategic prioritization of fiscal resources under martial law. The paper offers directions for strengthening the macroeconomic stability and financial resilience of Ukraine under martial law through the rational distribution of budget expenditures.